2023
DOI: 10.3390/cells12242846
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Barrier Dysfunction in Diarrhea-Predominant Irritable Bowel Syndrome (IBS-D) via Downregulation of Claudin-1

Karem Awad,
Christian Barmeyer,
Christian Bojarski
et al.

Abstract: Background: In patients with diarrhea-predominant irritable bowel syndrome (IBS-D), the diarrheal mechanisms are largely unknown, and they were examined in this study on colon biopsies. Methods: Electrophysiological measurements were used for monitoring functional changes in the diarrheic colon specimens. In parallel, tight junction protein expression was analyzed by Western blot and confocal laser-scanning microscopy, and signaling pathway analysis was performed using RNA sequencing and bioinformatics. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Enhanced macromolecule permeability was evidenced by a temperature-dependent augmentation in horseradish peroxidase (HRP) absorption within the PI-IBS group. This phenomenon indicates the activation of the transcytotic pathway in colonic mucosa functional assessments of PI-IBS patients, shown by increased HRP transport at 37 • C but not at 12 • C causing the immune activation [48]. Such macromolecule uptake signifies the translocation of antigens from the intestinal lumen to the mucosa, presenting significant pathological implications for mucosal balance when this process is prompted [1].…”
Section: Campylobacter Jejuni-induced Disruptions: Intestinal Permeab...mentioning
confidence: 98%
See 4 more Smart Citations
“…Enhanced macromolecule permeability was evidenced by a temperature-dependent augmentation in horseradish peroxidase (HRP) absorption within the PI-IBS group. This phenomenon indicates the activation of the transcytotic pathway in colonic mucosa functional assessments of PI-IBS patients, shown by increased HRP transport at 37 • C but not at 12 • C causing the immune activation [48]. Such macromolecule uptake signifies the translocation of antigens from the intestinal lumen to the mucosa, presenting significant pathological implications for mucosal balance when this process is prompted [1].…”
Section: Campylobacter Jejuni-induced Disruptions: Intestinal Permeab...mentioning
confidence: 98%
“…Specifically, individuals who experienced Campylobacter enteritis displayed an increase in enterochromaffin cells, intraepithelial lymphocytes and intestinal permeability, persisting for up to a year post-infection [7]. Disruption of the epithelial barrier often coincides with accentuated hypersensitivity in IBS, exacerbating abdominal pain symptoms within this condition [48] Prior clinical examination has demonstrated that patients with IBS-D and PI-IBS exhibit heightened permeability in the small intestine to 339 Da 51 -Cr-ethylenediaminetetraacetic acid (EDTA), in contrast to control subjects, which links the acute barrier disruption resulting from infection and the persistence of this barrier defect, aligning with the leaky gut concept, to the emergence of IBS symptoms [48].…”
Section: Campylobacter Jejuni-induced Disruptions: Intestinal Permeab...mentioning
confidence: 99%
See 3 more Smart Citations